2011
DOI: 10.1021/jp111382h
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Structural, Elastic, Electronic, and Optical Properties of Perovskite-type KMgH3 Crystals: Novel Hydrogen Storage Material

Abstract: We report a first-principles study of structural and phase stability in three different structures of perovskite-types KMgH(3) according to H position. While electronic and optical properties were measured only for stable perovskite-type KMgH(3), our calculated structural parameters are found in good agreement with experiment and other theoretical results. We also study the electronic charge density space distribution contours in the (200), (101), and (100) crystallographic planes, which gives better insight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 18 publications
(22 reference statements)
4
19
0
Order By: Relevance
“…It is well‐known that the refractive index or changes of the refractive index of the host medium influence the radiative lifetime , . While the refractive index of metal hydrides is probably 2, the refractive index of many oxides with yellow Eu 2+ emission is rather approximately 1.6 . An increase of n from 1.6 to 2 is thus expected to more than double the radiative decay rate, which is in agreement with the observed decay rates in hydrides.…”
Section: Eu2+‐doped Hydridessupporting
confidence: 80%
“…It is well‐known that the refractive index or changes of the refractive index of the host medium influence the radiative lifetime , . While the refractive index of metal hydrides is probably 2, the refractive index of many oxides with yellow Eu 2+ emission is rather approximately 1.6 . An increase of n from 1.6 to 2 is thus expected to more than double the radiative decay rate, which is in agreement with the observed decay rates in hydrides.…”
Section: Eu2+‐doped Hydridessupporting
confidence: 80%
“…The observation of shorter decay times than 1 μs can be explained by the presence of defects in these samples resulting in the promotion of a non‐radiative relaxation channel to the ground state, which shortens the lifetime of the excited state. Another explanation for a shorter lifetime could be a higher refractive index of about 2 for hydrides as compared to oxides or chlorides as already suggested as an explanation for the short lifetimes in pure hydrides by Kunkel et al…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Komiya et al [16] have reported the synthesis and decomposition of MMgH 3 (M = Na, K, Rb). The electronic structure, bonding and stability of typical perovskite-type hydrides MMgH 3 (M = Na, K, Rb) were theoretically investigated using first-principles methods [17][18][19][20][21][22]. CsCaH 3 is synthesized by Gingl et.al [23].…”
Section: Introductionmentioning
confidence: 99%